Development of Learning Management System-Based Blended Learning Model using Claroline in Higher Education - Tubagus, Munir; Muslim, Suyitno; Suriani, Suriani (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Learning Management System (LMS) is a learning process that utilizes computer information technology equipped with internet and multimedia telecommunications facilities (graphics, audio, video) in delivering material and interaction between instructors and learners. The purpose of this study is to develop blended learning Using Claroline as a learning tool that facilitates students in learning. To achieve the objective of the study the research uses a quantitative approach to collect data using pre and post tests and questionnaires. The sample in the study were students of economic Islamic consisting of two classes, with a total of 50 students enrolled in this study. The results show that the difference in the average pre-test and post-test score was -29.43720. While the t-test that tests Ho: pre-test = post-test gives a value of t = -37.43720 with a degree of freedom of 49. While the p-value for the two-sided test of 0,000 is smaller than α = 0.05. This data approves that the statistical hypothesis Ho: pre-test = post-test is rejected, meaning that the average pre-test and post-test scores are significantly different. The findings of this study can be used to recommend effective ways of learning and teaching using e-learning that can improve student learning outcomes in higher education. The implications of this research is to encourage teachers to use e-learning technology and facilitate students with the technology in improving academic learning outcomes.